Programming of Ukrainian National athletic team's preparation. - Yevhen Hutsol; Leonid Pylypei (Kharkiv State Academy of Physical Culture, 2020)
Purpose: theoretical and methodological substantiation of programming technology, attraction of innovative technologies in the Ukrainian National Athletic team's training process. Material & methods: the study was carried out among athletes of the national team of Ukraine, at least Master of Sports of Ukraine, by conducting a questionnaire, self-experiment, pedagogical observation and pedagogical experiment. The total number of respondents is 43 athletes. Among the participants of the experiment are the winners of the Olympic Games and world championships, champions and winners of the European championships, champions of Ukraine. Results: programming is presented in the article as a rigidly determined system of sequential and practiced operations within a certain time based on the developed control system project. Developed integrated models, the indicators of which are translated into ball points. The algorithm for constructing a system for attracting innovative technologies to the preparation of athletes is carried out on the basis of regression analysis with numerical coefficients according to the formulas. Conclusions: the proposed programming technology makes it possible to create an effective system for building an individual training process in the national team of Ukraine in athletics.